Crack properties, toughness and absorption evaluation of FRCC incorporating reclaimed asphalt pavement and crumb rubber as aggregates - Adeyemi Adesina (Elsevier, 2021)
The development and application of fibre-reinforced cementitious composites (FRCC) have evolved significantly over the last decade. However, there is a need to find innovative ways to improve the sustainability of composites. The production and transportation of the major binder (i.e. Portland cement) and aggregates used for FRCC consumes high energy and natural resources. Therefore, finding ways to incorporate recycled materials to replace these conventional components can be used to improve the sustainability of the FRCC. Also, the special micro silica sand used to produce certain types of FRCC is a major concern due to its limited availability and higher cost. On the other hand, there exist various waste materials that can be incorporated into FRCC as a replacement of either the binder or aggregate. Hence this current paper aims to investigate the performance of FRCC made with high volume fly ash as partial replacement of Portland cement, and reclaimed asphalt pavement/crumb rubber as replacement of the natural aggregates. The performance of the FRCC incorporating these recycled materials was evaluated in terms of its crack properties, toughness and sorption. Results from this study showed that the use of recycled crumb rubber is beneficial in terms of crack properties and lower sorption. The sorption of FRCC incorporating crumb rubber as the only aggregate was reduced by 31.8%. However, FRCC made with reclaimed asphalt pavement exhibited higher sorption and lower toughness.